Tradisi Reboan Sebagai Upacara Pitra Puja Pada Masyarakat Hindu Jawa Di Lampung (Kajian Komunikasi Sosio-Religius) - Anak Agung Oka Puspa; Kadek Hemamalini; Untung Suhardi; Wayan Kemenuh (Jayapangus Press, 2020)
The tradition of Hindus in Pujodadi Village, Pesawaran District, Lampung, the Reboan tradition is an important part of respecting their ancestors. For Hindus, the tradition of Reboan is not only carried out on certain counts which are usually carried out to honor ancestors by the general public, after a thousand days ancestral worship is still carried out. There are two identifications that formulate the problem in this study, namely the meaning of the Reboan tradition as the Pitra Puja Ceremony on the Javanese Hindu Society in Lampung and the implications of the Reboan tradition as the Pitra Puja Ceremony on the Javanese Hindu Society in Lampung. The thesis research method uses a type of qualitative descriptive research method with a phenomenological approach and data collection from the results of interviews, documentation, and observation, then the authors analyze the data with analysis in the field then do data reduction, data presentation, and finally the conclusion. The results of the study show that the meaning of the Reboan Tradition is an activity carried out to strengthen the kinship among Hindus in Pujodadi Lampung Village to improve Sraddha and Bhakti through the pitra puja ceremony. The implications of the Reboan Tradition for Javanese Hindus in Pujodadi in the socio-religious aspects show a better understanding of Sraddha and Bhakti. In the social aspect, the interaction between Javanese Hindus in Pujodadi is getting better which is shown by the increasing sense of kinship among the people.